Measuring Toxic Effects and Time to Treatment Failure for Nivolumab Plus Ipilimumab in Melanoma - Shoushtari, Alexander N; Friedman, Claire F; Navid-Azarbaijani, Pedram; Postow, Michael A; Callahan, Margaret K; Momtaz, Parisa; Panageas, Katherine S; Wolchok, Jedd D; Chapman, Paul B (JAMA oncology, 2018)
Nivolumab plus ipilimumab (nivo + ipi) is a standard treatment of advanced melanoma. Two randomized trials describe high objective response rates by Response Evaluation Criteria in Solid Tumors. The trials assessed toxic effects using the Common Terminology Criteria for Adverse Events (CTCAE), which may underestimate incidence of clinically significant immune-related adverse events (AEs). To describe detailed toxic effects and time to treatment failure of patients with melanoma treated with nivo + ipi in a prospective cohort. A cohort of 64 adults with advanced or unresectable melanoma were examined at a single tertiary cancer and enrolled in an expanded access program of nivo + ipi conducted from December 2014 to January 2016. Intravenous nivolumab (1 mg/kg) and ipilimumab (3 mg/kg) administered every 3 weeks for up to 4 doses, followed by nivolumab (3 mg/kg) every 2 weeks or pembrolizumab (2 mg/kg) every 3 weeks until unacceptable toxic effects, disease progression, or complete response. Clinically significant immune-related AEs were defined as CTCAE grade 2 or higher or any immune-related AEs requiring systemic steroids. Time to treatment failure was defined as the interval between initiating therapy and the earliest of clinical progression, new locally directed or systemic treatment other than anti-programmed cell death 1 protein (anti-PD-1) monotherapy, or death. Overall 64 adults with advanced or unresectable melanoma were enrolled (male to female ratio, 1:1; median [range] age, 56 [22-82] years); 25 patients (39%) received all 4 doses of nivo + ipi, and 31 patients (48%) received no maintenance anti-PD-1 therapy. Most who discontinued treatment (n = 31 [80%]) stopped because of toxic effects. Among those patients who were progression free at 12 weeks, time to treatment failure was similar between those who did or did not modify therapy for toxic effects. Fifty-eight patients (91%) had a clinically significant immune-related AE (median, 2/patient), and 46 patients (72%) required systemic steroids. Infliximab or mycophenolate was required in 16 patients (25%) for steroid-refractory immune-related AEs. Seven patients (11%) developed hyperglycemia, 32 patients (50%) had an emergency department visit, and 23 patients (36%) required a hospital admission related to an immune-related AE. Four of 31 patients (13%) who stopped combination therapy early for toxic effects developed a new, clinically significant immune-related AE more than 16 weeks after the last treatment. We observed a 91% incidence of clinically significant immune-related AEs leading to frequent emergency department visits, hospitalizations, and systemic immunosuppression. Immuno-oncology trials should routinely report these metrics. Most patients do not tolerate 4 doses of nivo + ipi; however, 4 doses may not be required for clinical benefit.